Student's Religious Character (Viewed From the Human Resource Management Perspective) - Ahmad Ansori; Husarida Husarida; Hasirah Hasirah (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Religious character is one of the characters that needs to be developed in the students to cultivate behavior that is in accordance with the teachings of Islam which based on the Qur'an and Hadith. This study aim to describe the teacher's role in improving the religious character of the students of Nurul Yaqin Elementary School. The method used in this research is a qualitative method with the type of field research. The subjects in this study were principals, teachers, parents, and students of Nurul Yaqin Elementary School. Data was collected through observation, interviews, and documentation. The data were analyzed using the stages of data collection, data reduction, data presentation, and drawing conclusions. Then the validity of the data is carried out using the triangulation technique. The results showed that the teacher's role in improving the religious character of students at Nurul Yaqin Elementary School was the teacher as an educator and a role model for students, which  collaborating with students' parents. As educators, teachers always teach students to behave in accordance with the teachings of Islam. As an example, through their behavior and actions the teachers reflects on religious values as part of their life. Collaborating with the parents is needed because when students are at home, parents are fully responsible to encourage the religious character of their children